Does distance still matter for agricultural trade? - Ebeke, Christian; Etoundi, Mireille Ntsama (International Food Policy Research Institute, 2016)
This paper quantifies the average effect of distance on bilateral agricultural trade using a large sample of countries. We focus on identifying time-varying effects of distance on trade to test whether the marginal effect has gradually diminished in recent years; to do this, we use a sample that includes more than 200 countries and spans the period 1995-2013. A variety of robustness checks and model specifications are used. The results suggest that the “distance effect” significantly explains bilateral agricultural trade flows.